Reproductive outcomes in women with unicornuate uterus undergoing in vitro fertilization: a nested case-control retrospective study - Yanrong Chen; Victoria Nisenblat; Puyu Yang; Xinyu Zhang; Caihong Ma (BMC, 2018)
Abstract Background Unicornuate uterus, a congenital uterine malformation resulting from unilateral maldevelopment of Mullerian duct, is more prevalent in women with infertility. Owing to relative rarity of the condition, the evidence on the associated reproductive outcomes is derived from small heterogeneous studies that report different clinical endpoints and often do not account for the anatomical variations of unicornuate uterus. The aim of this study was to evaluate the embryological and clinical outcomes following IVF-ICSI treatment in women with unicornuate uterus without rudimentary functional cavity (ESHRE-ESGE class IVb). Methods Retrospective nested case-control study comprised 342 women with unicornuate uterus and 1026 matched controls who underwent IVF-ICSI cycles between October 2012 and October 2016. Cumulative live birth rate upon one complete IVF cycle, including transfers of all resulting embryos was considered as a primary outcome measure. Results Baseline characteristics were comparable between the unicornuate uterus and control groups except for higher rate of primary infertility in unicornuate uterus. Ovarian response to stimulation did not differ between the groups. Transfer of day-3 embryos in fresh cycle resulted in lower clinical pregnancy rate (35.9% vs. 43.9%, p = 0.028) and live-birth rate (26.9% vs. 35.2%, p = 0.017) per transfer, but the difference was not observed when either cleavage frozen-thaw embryos or blastocysts were transferred. Implantation rate was lower and miscarriage rate was higher in women with unicornuate uterus but the difference between the groups did not reach statistical significance. Transfer of cleavage embryos resulted in significantly higher miscarriage rate and lower live-birth rate in fresh versus frozen-thaw cycles in each group, whereas fresh and frozen-thaw blastocyst embryos had comparable outcomes. Upon completion of one IVF-ICSI cycle, the cumulative pregnancy rate (53.1% vs. 65.7, p < 0.001) and cumulative live birth rate (42.4% vs. 54.6%, p < 0.001) were significantly lower in women with unicornuate uterus compared to those in women with normal uterus. Cumulative outcomes were superior when embryos were cultured to blastocyst stage. Conclusions Women with unicornuate uterus have lower clinical pregnancy and live birth rate after IVF-ICSI treatment compared to women with normal uterus. The treatment outcomes are improved with blastocyst culture, which warrants evaluation in prospective setting.